Terrorism and WMDs awareness and response - Pichtel, John (CRC Press, 2016)
Terrorism and WMD's, Second Edition provides a comprehensive, up-to-date survey of terrorism and weapons of mass destruction (WMDs). Terrorist weapons and delivery methods are becoming increasingly sophisticated; as such, this book focuses on the chemistry and biology of WMDs, the development and history of their use, and human health effects of such weapons.